Partial molar volumes of organic solutes in water. XXVIII. Three aliphatic poly(ethylene glycols) at temperatures T = 298 K–573 K and pressures up to 30 MPa. (June 2017) - Cibulka, Ivan
Graphical abstract: Highlights: Standard molar volumes of three poly(ethylene glycols) in water are presented. Data were obtained in the range T from (298 to 573) K and p up to 30 MPa. Data are analyzed and compared with those of similar solutes. Abstract: Densities of dilute aqueous solutions of three poly(ethylene glycols): 3-oxapentane-1, 5-diol (diethylene glycol), 3, 6-dioxaoctane-1, 8-diol (triethylene glycol), and 3, 5, 9-trioxaundecane-1, 11-diol (tetraethylene glycol) measured in the temperature range from (298 to 573) K and at pressures up to 30 MPa using an automated flow vibrating-tube densimeter are reported. Standard molar volumes were evaluated from the measured data. Present data complement both the previous measurements performed at atmospheric pressure in the temperature range from (278 to 343) K and the data already available for the first member of the homologous series (ethylene glycol). A comparison with data previously measured for the homologous series of linear aliphatic polyethers (poly(ethylene glycol) dimethyl ethers, glymes), diethylene glycol monomethyl ether (3, 6-dioxaheptan-1-ol), and selected alkane-α, ω-diols is presented.